v.1 - Peters, B. Guy (ed.) (London, 2015)
Fundamental Works, History of Public Administration, Organizations in Public Administration, Reforming the Public Sector, The Future of Public Administration.
Volume I: Fundamental Issues in Public Administration
Keywords: Public administration